A study on the marine ecological security assessment of Guangdong-Hong Kong-Macao Great Bay Area. (March 2022) - Gao, Le-hua; Ning, Jing; Bao, Wu-lan-tuo-ya; Yan, An; Yin, Qiao-rong
Abstract: The construction of world-class Bay makes the marine ecology in Guangdong-Hong Kong-Macao Great Bay Area in risk. Based on the DPSIR index framework, Lotka-Volterra symbiosis model is applied to calculate symbiosis degree between coastal socio-economic system and marine ecosystem in 9 coastal cities. It is found that the marine ecological pressure in this area have not been reversed in recent 20 years. Most cities are in the stage that socio-economic development and marine ecological damage coexist. In Shenzhen, Guangzhou, Dongguan and Zhongshan, the damaged marine ecology has begun to restrain the further expansion of economy and society. The massive population agglomeration in Hong Kong, Macao and other places has caused serious marine ecological stress. It is urgent to improve the marine ecological security by cultivating ecological industrial system and industrial clusters, establishing a land-sea ecological restoration, promoting joint-protection and co-governance across different administrative regions. Graphical abstract: Unlabelled Image Highlights: Relationship between coastal socio-economic system and marine ecosystem was revealed. The marine ecological security was evaluated by Lotka-Volterra symbiosis model. DPSIR system was constructed with marine ecological, economic, and social indicators. Suggestions for improving marine ecology in the Greater Bay Area were proposed.